AIZA LANGUAGE BEHAVIOR IN DAILY LIFE (PSYCHOLINGUISTIC STUDY) - Goziyah; Atikah Rahmah Agustin (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to describe and analyze the language behavior of a child named Aiza in her daily activities from a psycholinguistic perspective. The focus of the study includes word choice, sentence structure patterns, speaking style, and the contexts of language use when Aiza interacts with her parents, peers, and when engaging in self-talk. This research employs a qualitative approach using a case study method. Data were collected through direct observation, informal interviews with the parents, and documentation in the form of field notes and recordings of the child’s utterances. Data analysis was conducted descriptively through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that Aiza’s language behavior reflects a comprehensive language development, encompassing pragmatic, syntactic, and cognitive aspects. She is able to adjust her vocabulary, construct both simple and compound sentences, and modulate her speaking style according to the context, including when speaking to herself. This pattern underscores language as a tool for thinking and cognitive mediation in line with Vygotsky’s theory, particularly the concepts of ZPD and scaffolding, with social interactions with parents, siblings, and the surrounding environment enriching her vocabulary, sentence structure, and pragmatic abilities.